Social images about adolescents in residential care: What do the neighbors say? (Research, Society and Development, 2021)
The aim of the study was to investigate the social images that neighbors of residential services attribute to institutionalized adolescents. This is a study with a cross-sectional design, descriptive in nature and with a quantitative and qualitative approach to data. The participants were 100 neighbors (adults and young people), of both sexes, from three residential care institutions in the metropolitan region of Belém-Pa, aged between 16 and 85 years old (M= 41.5, SD= 17.1). The instruments used were a questionnaire on social images, a questionnaire on neighborhood quality, a semi-structured interview script and a field diary. Were realized descriptive analysis, valence analysis, t-test for the paired sample, cluster analysis and content analysis. The results revealed that negative attributes were more associated with institutionalized adolescents, especially in neighborhoods 2 and 3, where there was weakness in the interaction with neighbors. The relationships established can influence the maintenance or deconstruction of social images about institutionalized adolescents. Their participation in the community/neighborhood can contribute to the deconstruction of negative social images about them. It is also suggested that adolescents take the condition of institutionalization as something that gives them a social identity, which marks them as different from society. The fragility of the relationship between the host services and the neighborhood reinforces negative social images and makes it difficult to exercise community coexistence.